An introduction to health planning for developing health systems - Green, Andrew, 1952-; Green, Andrew, 1952- (New York ; Oxford : Oxford University Press, 2007)
Andrew Green explains the importance of health planning in both developing regions such as Africa, and those in transition, such as Central and Eastern Europe. This book stresses the importance of understanding the national and international context in which planning occurs and analyses the major policy issues.
Previous ed.: published as An introduction to health planning in developing countries. 1999.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Health planning -- Developing countries; National health services -- Developing countries